Herbal Soap Formulation as Anti-Bacterial in the Context of Increasing the Community's Healthy Living Movement - Nuryati, Anik; Setiawan, Budi; Martsiningsih, M. Atik (Syntax Corporation Indonesia, 2024)
Plants have long been used by Indonesian communities for medicinal purposes, including herbal soaps. The number of herbal soap producers has increased, offering various types made from natural ingredients such as lemongrass, clove, and cinnamon. However, the concentration of essential oils in herbal soaps can vary significantly across brands. This study aimed to formulate an herbal soap as an antibacterial agent by determining the minimum concentration of essential oils (clove, cinnamon, and lemongrass) needed to inhibit the growth of Staphylococcus epidermidis and Pseudomonas aeruginosa. The research employed a Post-test Only Control Group Design and was conducted at the Microbiology Laboratory of Health Analysts in Yogyakarta from January to October 2020. The study tested essential oils at concentrations of 0.5%, 1.0%, 1.5%, and 2.0%. The inhibition zones were measured to evaluate effectiveness. Results showed that the inhibition zones for lemongrass oil at concentrations of 0.5%, 1%, 1.5%, and 2% against Pseudomonas aeruginosa were 6.85, 7.61, 7.89, and 8.92 mm, respectively. Cinnamon oil exhibited larger inhibition zones against both Pseudomonas aeruginosa and Staphylococcus epidermidis. Clove oil had less antibacterial effectiveness compared to cinnamon. Cinnamon oil at 2.00% concentration was very effective against Staphylococcus epidermidis, while 1.50% concentration was adequate for Pseudomonas aeruginosa.